Piezoelectric based broadband nonlinear vibration energy harvester using multiple magnets - Asneh, Ag. M. Asmulizan; Muthalif, Asan G. A.; Wahid, Azni N.; Haja Mohaideen, Ahmad Jazlan; Mohamad Hanif, Noor Hazrin Hany (International Journal of Industrial Electronics and Electrical Engineering (IJIEEE), 2017)
The advancement of technology has made low-powered devices such as wireless sensor network powered using small battery become possible. However, this type of battery has limited lifespan and needed to be changed frequently which is not convenient when placed in remote area or harsh environment. Therefore, devices that can harvest energy from their surrounding are preferred. One of the famous method is by using piezoelectric transducer to scavenge ambient vibration energy. However, the piezoelectric harvester (PEH) usually has small bandwidth that it can operate. This paper proposed a PEH in the form of cantilever beam with a tip mass along with multiple fixed magnets in certain configuration. The proposed design uses external force by magnet to alter its stiffness and then due the nonlinearity effect introduced by magnets, the operating bandwidth of the PEH is increased. With proper configuration, the proposed design has improved bandwidth compared to PEH without any magnet. It is also found that power output of proposed PEH is relatively higher than conventional PEH which is about 1314 µW where this value is enough to power up low-powered device. In addition, the power per frequency of proposed PEH is 81.59 µW/Hz, which is about 64 percent higher than the PEH without any magnets